2020
DOI: 10.1039/d0nj01719a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, DFT studies, fabrication, and optical characterization of the [ZnCMC]TF polymer (organic/inorganic) as an optoelectronic device

Abstract: A novel carboxymethyl cellulose zinc thin film [ZnCMC]TF was fabricated using the sol–gel technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…In addition, Cr-Ni OSC complexes are observed to exhibit energy band gaps of ~1.87 eV which nominates it for use in visible light communications as signal receivers 3 . Moreover, carboxymethyl cellulose zinc thin films which were fabricated using the sol-gel technique and widely tested are found to be ideal materials for use in producing photosensors and solar cells 6,7 . As nanoparticles, Co-Al oxides are reported promising alternative materials for improving the power conversion efficiency of solar cells and for obtaining clean and renewable energy 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Cr-Ni OSC complexes are observed to exhibit energy band gaps of ~1.87 eV which nominates it for use in visible light communications as signal receivers 3 . Moreover, carboxymethyl cellulose zinc thin films which were fabricated using the sol-gel technique and widely tested are found to be ideal materials for use in producing photosensors and solar cells 6,7 . As nanoparticles, Co-Al oxides are reported promising alternative materials for improving the power conversion efficiency of solar cells and for obtaining clean and renewable energy 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Again, the product was also defined by the FTIR spectral bands 54–56 observed at frequency 3636 cm −1 that define the −OH group in BTB and this band is shifted to 3430 cm −1 ; so this indicates the oxidation occurs in the hydroxyl group. Finally, the band found at 1593 cm −1 54–56 characterizing the carbonyl group with related ketones; a strong band occurs at 3157 cm −1 characterizing the CH 2 group 57–59 in the case with BTB while it seems to be the weak band at 2954 cm −1 in the case of keto‐BTB characterizing the −CH group 60–61 . Enhancement of the OH group's absorption band at a wavenumber of 1593 cm −1 in the product's FTIR spectra that mean oxidation of the OH group present in BTB dye to its corresponding keto‐forms as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The surface charge of nanoparticles is pH-dependent and raises the intrinsic properties of the oxides on their surface. Observed agglomeration could be due to this fact [ 25 , 26 , 36 ]. The results showed that the treatment of Wistar rats with different concentrations of Al 2 O 3 nanoparticles led to changes in bone tissue.…”
Section: Discussionmentioning
confidence: 99%